In vivo inhibitory effect of suberoylanilide hydroxamic acid combined with sorafenib on human hepatocellular carcinoma cells (Brazilian Journal of Pharmaceutical Sciences, 2020)
The present study aimed to investigate the in vivo inhibitory effect of histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) combined with sorafenib on human hepatocellular carcinoma HCCLM3 cells. The nude mice transplanted with HCCLM3 cells were randomly divided into control, SAHA, sorafenib and SAHA+sorafenib groups. The nude mice in the later 3 groups were intragastrically administrated with SAHA (10 mg·kg-1·day-1), sorafenib (10 mg·kg-1·day-1) and SAHA (10 mg·kg-1·day-1) combined with sorafenib (10 mg·kg-1·day-1), respectively, for successive 20 days. Finally, the inhibition rate of tumor was measured. The expressions of MEK1/2, p-ERK1/2, Cyclin D1, Bcl-2, Bax, p53, MMP2, MMP-9 and uPA in tumor tissues were determined. Results showed that, compared with SAHA and Sorafenib groups, in SAHA+sorafenib groups the inhibition rate of tumor was significantly increased (P < 0.05), the expression levels of MEK1/2, p-ERK1/2, Cyclin D1, Bcl-2, MMP-2 and MMP-9 and uPA protein in tumor tissues were significantly decreased, respectively (P < 0.05), and the expression levels of Bax and p53 protein were significantly increased, respectively (P < 0.05). In conclusion, compared with single drug, SAHA combined with sorafenib can enhance the inhibitory effects on HCCLM3 xenografts in nude mice.